IMPLICATION OF PROBLEM BASED LEARNING ON ENVIRONMENTAL POLLUTION SUBJECT TO IMPROVE STUDENTS’ CRITICAL THINKING SKILL AT CLASS X MIA 3 OF SMA NEGERI 3 SURAKARTA - Suwarno, Hesti Retno Puji Astuti, Baskoro Adi P (P Biologi FKIP UNS Surakarta, 2015)
The purpose of this research is to improve students? critical thinking skill on Environmental Pollution Subject at class X MIA 3 of SMA Negeri 3 Surakarta. The research is a Classroom Action Research with 2 cycles of action. Each cycle consist of 4 phases which is planning, acting, observing, and reflecting. The result of the observations showed, 1) interpretation skill 43.97%, 2) analysis 29.31%, 3) evaluation 32.76%, 4) inference 43.10%, 5) explanation 53.45%, and 6) self-regulation 52.59%. Average of students? critical thinking skill procentage is 42,53%.The method of data collection is through observation, tests, and documentation. Technical analysis of data is technical qualitative descriptive. Data validation is use triangulation methods.The results of the application of Problem Based Learning on Environmental Pollution Subject showed an increase of students? critical thinking skill. Students? critical thinking skill in the first cycle is 70,83%. Students? critical thinking skill in the second cycle is 75%.Based on the result of the research, we can conclude that the application of Problem Based Learning on Environmental Pollution Subject in general can improve students? critical thinking skill at class X MIA 3 of SMA Negeri 3 Surakarta, despite the increase that occurs varies in each cycle. Keywords : Critical Thinking Skill, Problem Based Learning